The Jury Is Still Out on the Benefits and Harms of Methylphenidate for Children and Adolescents With Attention‐Deficit/Hyperactivity Disorder. Issue 4 (13th July 2018) - Storebø, Ole Jakob; Faltinsen, Erlend; Zwi, Morris; Simonsen, Erik; Gluud, Christian
Abstract : Much remains unclear about the benefits and harms of methylphenidate for children and adolescents with attention‐deficit/hyperactivity disorder (ADHD). Between 2012 and 2018, we conducted two Cochrane systematic reviews on methylphenidate for ADHD. This article explores the main findings in relation to evidence‐based practice and our current understanding of ADHD.1 2